THE ROLE OF DIGITAL TECHNOLOGIES IN THE SUSTAINABLE DEVELOPMENT OF PRECISION AGRICULTURE - Alisher Ismailov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The article describes modern problems of agriculture, trends in their development and elements of digital agriculture.